Intranasal glioma (Nasal heterotopia): A rare cause of nasal polyp in neonates - Vikram Narang; Saveena Jindal; Bhavna Garg; Harpreet Kaur; Ankita Soni (Wolters Kluwer Medknow Publications, 2022)
A 3-month-old boy presented with an intranasal polypoidal mass protruding out of the nostril which was present since birth and growing slowly. The mass was non-pulsatile and soft to firm in consistency. It did not increase in size on coughing, crying, or compression of the jugular vein. Magnetic resonance imaging and contrast-enhanced computed tomography (CT) revealed a lobulated well-circumscribed soft tissue mass in the left nasal cavity with no intracranial communication. Complete surgical excision of the mass was carried out via an intranasal endoscopic approach. Histopathological examination confirmed the diagnosis of intranasal glioma.